Literature Review: Peran Komunikasi Interpersonal dalam Menjembatani Gap Generasi pada Era Digital di Dunia Kerja - Yeski Putri Utami; Aura Balqis Nur Azizah; Putri Stevanie Purba (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The generational gap in the digital workplace has become increasingly apparent due to differences in work values, communication media preferences, and levels of technological adaptation among age groups. These differences often affect coordination effectiveness, the quality of working relationships, and intergenerational collaboration. This study aims to analyse the role of interpersonal communication in bridging generational gaps in the digital work environment. A Systematic Literature Review (SLR) method was employed by examining national publications from 2017 to 2025 related to interpersonal communication, generational issues, and the digital workplace. The literature selection process was conducted systematically through identification, screening, and synthesis stages. The findings indicate that generational gaps are primarily driven by disparities in digital literacy, variations in communication styles, and differing work expectations and values. The synthesis reveals that interpersonal communication—through two-way dialogue, empathy, active listening, and adaptive communication styles—plays a significant role in fostering mutual understanding and reducing social distance between generations. This study confirms that strengthening interpersonal communication competencies and adopting inclusive communication practices are essential strategies for creating harmonious, effective, and digitally responsive intergenerational working relationships.